Aplikasi Peromohonan Cuti Pegawai pada Dinas Pariwisata Kota Palembang - Atuti, Tri Widiya; Solikin, Imam; Komlasari, Dinny (Jurnal Ilmiah Teknologi Informasi dan Robotika, 2025)
This research concerns leave applications at the Dinas Pariwisata Palembang City. Currently the leave application process at the Dinas Pariwisata is carried out procedurally from table to table. This process is very inefficient because it requires a long time and accuracy in finding leave data. This research uses the waterfall system development method in its development process, namely Requirements Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The data collection methods used were observation, interviews and literature study methods. The results of this research are "Responsive Web Based Employee Leave Application for the Dinas Pariwisata Palembang City". It is hoped that the results of this research can make it easier for employees to process leave applications.